PEMODELAN ADDIE DALAM PENGEMBANGAN KURIKULUM 13 PADA PEMBELAJARAN BAHASA INGGRIS TINGKAT SEKOLAH DASAR BERBASIS ANDROID - Luluk Elvitaria Elvitaria; Debi Setiawan; Lasiah Susanti; Syafrizal Syafrizal (LPPM Universitas Abdurrab, 2023)
The proliferation of science and technology that is so rapid today supports and makes it easier for all the activities in various areas of human life, one of them being education. The K–13 curriculum requires schooling. The excess K–13 is to require students to be more independent, creative, and innovative, emphasizing character education. And the judgment process is made up of all the aspects of attitude, activity, skill, and knowledge. English is essential to study and be understood by the students because of the challenge of global development, and one of its supporting tools is mastery of English as a communication medium in the global and international world. Purpose: This study made it easier for students to tackle mainly the English learning process pronunciation in the form of interactive systems by applying speech and voice technologies recognition. Data collection from library studies, interviews, and observatories Methods of quantitative analysis are used in this research process for testing. Testing systems using black box testing with a successful walk and user acceptance test (UAT) and getting an average of 85% of student responses The results of this study prove that interactive system applications generate 86% and 84% of the result of media appropriations and material content, respectively, that are perfectly feasible in the learning process.